Feminism in Harry Bradbeer’s Movie 'Enola Holmes' (Universitas Negeri Semarang, 2022)
From ancient times to the present, women have been subjected to a great deal of discrimination. Discrimination against women is predominant in the movie Enola Holmes. This statement attracts attention since women are frequently perceived as weak and devalued because women rely on males and are rarely free to do. Through the movie Enola Holmes, which is backed by feminist theory (Collins, 2000), this study intends to explore information about the varieties of feminism that occur in the movie. This study applies a qualitative descriptive method, which is commonly used to investigate social problems of phenomena. The data is taken from several pictures, dialogues, and monologues from the Enola Holmes movie and then analysis done contextually and theoretically. The researchers found that liberal feminism was the most prevalent, it shows oppressed women in any situation. In contrast, Radical Feminism is a minor one, social actions are related to a social system that place men as the primary power holders and dominates in various roles. Postmodern feminism and Critical Race Feminism data are not found in the movie, because those kinds of feminism did not appear in the 19th century.